Nutrition and Exercise in a Case of Carnitine Palmitoyl-Transferase II Deficiency - Parimbelli, Mauro; Pezzotti, Elena; Negro, Massimo; Calanni, Luca; Allemano, Silvia; Bernardi, Marco; Berardinelli, Angela; D’Antona, Giuseppe (Frontiers in Physiology, 2021)
In the mild subtype of inherited carnitine palmitoyl-transferase II (CPTII) deficiency, muscular mitochondrial fatty acid β-oxidation is impaired. In this condition, interventions involve daily dietary restriction of fats and increase of carbohydrates, whereas physical exercise is commonly contraindicated due to the risk of muscle pain and rhabdomyolysis. We present the case of 14-years-old female with CPTII deficiency who underwent 6-months 3-days/week 1 hour/session on an unsupervised exercise training, including interval and resistance exercises, after diet assessment and correction. Before/after intervention, resting metabolic rate (RMR) and respiratory quotient (RQ) were measured by indirect calorimetry and cardiopulmonary exercise test (CPET, 10 W/30 secs to exhaustion) was performed. Interval training consisted of 1-minute run/5min walk (for 15 min progressively increased to 30 min). During efforts the heart rate was maintained over 70% HRmax corresponding to respiratory exchange ratio (RER) of 0.98. Resistance training included upper/lower split workouts (3 sets of 8 reps each, 2 min rest between sets). Blood CK was checked before and 36 hrs two training sessions chosen randomly without significant difference. After training RMR increased (+8,1%) and RER lowered into the physiological range (from 1.0 to 0,85). CPET highlighted an increase of peak power output (+16,7%), aerobic performance (VO2peak, 8,3%) and anaerobic threshold (+5,7%), oxygen pulse (+4,5%) and a much longer isocapnic buffering duration (+335%). No muscle pain or rhabdomyolysis was reported. Results from our study highlight that a training based on short-duration high-intensity improves overall metabolism and aerobic fitness, thus being feasible in a case of CPTII deficiency.